2012
DOI: 10.1007/s10886-012-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Chemically Mediated Interactions in Agricultural Soils to Enhance the Control of Crop Pests and to Improve Crop Yield

Abstract: In most agro-ecosystems the organisms that feed on plant roots have an important impact on crop yield and can impose tremendous costs to farmers. Similar to aboveground pests, they rely on a broad range of chemical cues to locate their host plant. In their turn, plants have co-evolved a large arsenal of direct and indirect defense to face these attacks. For instance, insect herbivory induces the synthesis and release of specific volatile compounds in plants. These volatiles have been shown to be highly attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 105 publications
0
29
0
1
Order By: Relevance
“…When released by insect-damaged maize roots, (E)-β-caryophyllene was identified as the main belowground chemical attractant for entomopathogenic nematodes (Heterorhabditis megidis Poinar, Jackson & Klein and Heterorhabditis bacteriophora Poinar) in laboratory and field experiments (Rasmann et al 2005;Turlings 2007, 2008;Hiltpold et al 2010a). The discovery that a root-emitted signal produced by plants infested by D. virgifera virgifera larvae is able to recruit organisms of the third trophic level as an indirect plant defence mechanism led to the development of new crop protection strategies using entomopathogenic nematodes as biological control agents to reduce D. virgifera virgifera emergence and root damage in the field (Hiltpold et al 2010c;Hiltpold and Turlings 2012). Several attempts to improve the searching efficiency of entomopathogenic nematodes were made, notably by selecting an entomopathogenic nematode strain for enhanced responsiveness to (E)-β-caryophyllene (Hiltpold et al 2010a, b) or by genetically engineering a maize variety that had lost the ability to produce (E)-β-caryophyllene in order to restore the release of the sesquiterpene signal (Degenhardt et al 2009).…”
Section: Plant Roots Release Vocs Involved In Belowground Biotic Intementioning
confidence: 99%
“…When released by insect-damaged maize roots, (E)-β-caryophyllene was identified as the main belowground chemical attractant for entomopathogenic nematodes (Heterorhabditis megidis Poinar, Jackson & Klein and Heterorhabditis bacteriophora Poinar) in laboratory and field experiments (Rasmann et al 2005;Turlings 2007, 2008;Hiltpold et al 2010a). The discovery that a root-emitted signal produced by plants infested by D. virgifera virgifera larvae is able to recruit organisms of the third trophic level as an indirect plant defence mechanism led to the development of new crop protection strategies using entomopathogenic nematodes as biological control agents to reduce D. virgifera virgifera emergence and root damage in the field (Hiltpold et al 2010c;Hiltpold and Turlings 2012). Several attempts to improve the searching efficiency of entomopathogenic nematodes were made, notably by selecting an entomopathogenic nematode strain for enhanced responsiveness to (E)-β-caryophyllene (Hiltpold et al 2010a, b) or by genetically engineering a maize variety that had lost the ability to produce (E)-β-caryophyllene in order to restore the release of the sesquiterpene signal (Degenhardt et al 2009).…”
Section: Plant Roots Release Vocs Involved In Belowground Biotic Intementioning
confidence: 99%
“…These metabolites, when released from leaves, flowers, and fruits into the atmosphere, and from roots into the soil, have key roles in the attraction of pollinators [2] and seed dispersers [3,4], above-and belowground defense against herbivores [5][6][7][8], protection against pathogens [9,10], and plant-plant signaling [11,12]. Certain VOCs are also able to protect plants against abiotic stresses, such as high light, temperature, or oxidative stress [13][14][15].…”
mentioning
confidence: 99%
“…Studies using various bioassay approaches have shown that chemical cues from intact roots (Johnson et al 2004), solvent-based root extracts (Kamm and Buttery 1984, Tapia et al 2005, Bergh et al 2011, or root volatiles (Matsumoto and Thorsteinson 1968, Jones and Coaker 1979, Soni and Finch 1979, Koštál 1992, Wenke et al 2010, Manosalva et al 2011) from host plants elicited positive behavioral responses by root-feeding insects. Chemically mediated interactions between root-feeding insects and their speciÞc host plants were reviewed most recently by , Hiltpold and Turlings (2012), and Johnson and Nielsen (2012). Bergh et al (2011) showed that recently eclosed grape root borer neonates were recorded more frequently on or near Þlter paper discs treated with ethanol-based grape root extracts than untreated discs or those treated with a nonhost (apple) root extract in single extract bioassays.…”
mentioning
confidence: 99%